Mindful care: the pilot of a new mental health service for young people who are looked after away from home in Moray - Jenny Makinson; Christopher Wiles; Debbie Jones; Sheila Erskine (Scottish Journal of Residential Child Care)
It is well documented that children and young people who are looked after away from home have significantly high rates of mental health problems coupled with poor psychological adjustment and general levels of emotional wellbeing (McCann et al., 1996; Minnis & Devine, 2001; Minnis et al., 2001; Hill & Watkins, 2003; Meltzer et al., 2004; Rodrigues, 2004; Ford et al., 2007). A range of conduct, emotional and hyperkinetic disorders appear most common in this population, and co-morbidity rates are noticeably high (Meltzer et al., 2004). Furthermore, only a small proportion of this at-risk population is likely to be accessing Child and Adolescent Mental Health Services (CAMHS) (Dimigen et al., 1999). Barriers to successful CAMHS input occur at several stages within the process, from identification and referral of mental health problems through to the engagement of the young person and effective interventions for their specific constellation of behaviours and symptoms (Blower et al., 2004; Mount, Lister & Bennun, 2004).